A qualidade da auditoria interna e a legitimidade da gestão das instituições federais de ensino superior brasileiras - Mutti, Cláudia Silveira Thys (Universidade do Vale do Rio dos Sinos, 2019)
This study analyzes the quality of internal audit at Brazilian federal graduation institutions (IFES) as an explaining factor of the annotations from state controlling organisms, contributing to public organization management’s legitimation. Theoretical literature and empirical studies are the basis for the research hypothesis: a smaller number of annotations from state controlling organisms, influenced by a better quality internal audit, reinforces the public organization management’s legitimacy. This hypothesis is tested empirically through econometric procedures using primary and secondary data from 40 federal graduation institutions in years 2015, 2016 and 2017, representing 40% of the total population of Brazilian IFES, resulting in a sample size of 67 observations. Discrepant observation checks are carried out to prevent any offshoot from outlier results, furthermore it’s decided to proceed with winsorizing transformation at 2.5% and 97.5%. A correlation test is ran between the independent variables willing to evaluate the strength of their associations. After identifying no strong relation, the research hypothesis test is carried out using the logical regression method. At all performed regressions it is observed a negative effect between the state controlling organism annotations and the quality of internal audit. The conclusion is that the research results confirm the hypothesis that a smaller number of annotations from the state controlling organism, influenced by a better quality internal audit, reinforces the public organization management’s legitimacy.
Keywords: Legitimidade; Governança; Auditoria Interna; Legitimacy; Governance; Internal Audit; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis